1986
DOI: 10.1002/ddr.430080111
|View full text |Cite
|
Sign up to set email alerts
|

Levocabastine (R 50547): The prototype of a chemical series of compounds with specific H1‐antihistaminic activity

Abstract: Stokbroekx R.A., M.G.M. Luyckx, J.J.M. Willerns, M. Janssen, J.O.M.M. Bracke, R.L.P. Joosen, and J.P. Van Wauwe: Levocabastine (R 50547): The prototype of a chemical series of compounds with specific HI-antihistaminic activity. Drug Dev. Res. 8:87-93, 1986.The synthesis and the histamine HI antagonism of four racemates of l-[cyano-4-(4-fluorophenyl)cyclohexyl]-3-methyl-4-phenyl-4-piperidinecarboxylic acid, termed R 48756, R 49389, R 49429, and R 49549, are described. R48756 (cabastine) was found to be the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Therefore, the results showed that Cop inhibit dextran-induced plasma extravasation. On the other hand, a selective antihistaminic that lacks antiserotonin activity failed to block dextran-induced vascular permeability changes, ruling out a participating role for histamine in this type of inflammatory reaction [ 26 ]. Therefore, the weak activity observed for Cop on carrageenan-induced paw oedema at the 1 h could be attributed to the participation of histamine in carrageenan-induced paw oedema.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the results showed that Cop inhibit dextran-induced plasma extravasation. On the other hand, a selective antihistaminic that lacks antiserotonin activity failed to block dextran-induced vascular permeability changes, ruling out a participating role for histamine in this type of inflammatory reaction [ 26 ]. Therefore, the weak activity observed for Cop on carrageenan-induced paw oedema at the 1 h could be attributed to the participation of histamine in carrageenan-induced paw oedema.…”
Section: Discussionmentioning
confidence: 99%
“…Affiliation of particular compounds with the groups of biological activity was established based on literature data (Van der Brook et al, 1948;Chinn and Smith, 1955;Marshall, 1955;Loew et al, 1967;Witiak et al, 1971;Brimblecombe et al, 1975a, b;Ebnöther and Weber, 1976;Martin and Romer, 1978;Bradshaw et al, 1979;Uzan et al, 1979;Daly et al, 1980;Van Wauwe et al, 1981;Wauquier and Niemegeers, 1981;Barnett et al, 1984;Takabatake et al, 1985;Stokbroekx et al, 1986;De Vos et al, 1987;Juhlin et al, 1987;Grant et al, 1990;Tasaka et al, 1990;Piwinski et al, 1991;Canonica et al, 1992;La Blaye et al, 1992;Jannssens and Howarth, 1993;Jannssens, 1993;Danysz, 1994;Walczynski et al, 1999aWalczynski et al, c, 2000Kemmritz, 2003;Swiader et al, 2004). In the qualitative analysis, lipophilicity of the examined compounds (log P) was additionally used.…”
Section: Structures Of the Examined Compounds 1-49mentioning
confidence: 99%
“…The following group codes were assigned to them a priori: I1 (for compounds 34-39, first generation drugs; Van der Brook et al, 1948;Chinn and Smith, 1955;Marshall, 1955;Loew et al, 1967;Witiak et al, 1971;Ebnöther and Weber, 1976;Martin and Romer, 1978;Uzan et al, 1979;Stokbroekx et al, 1986;Grant et al, 1990;Tasaka et al, 1990;Le Blaye et al, 1992;Danysz, 1994;Kemmritz, 2003;Swiader et al, 2004); I2 (for compounds 40-42, second generation drugs; Van Wauwe et al, 1981;Wauquier and Niemegeers, 1981;Barnett et al, 1984;De Vos et al, 1987;Juhlin et al, 1987;Piwinski et al, 1991;Canonica et al, 1992;Jannssens and Howarth, 1993;Jannssens, 1993); II (for compounds 43-45, with anti-H 2 activity; Brimblecombe et al, 1975a, b;Bradshaw et al, 1979;Daly et al, 1980;Takabatake et al, 1985); and A [thiazolederivative compounds 46-49 with H 1 agonistic activity (Walczynski et al, 1999a)].…”
Section: Modelmentioning
confidence: 99%
“…Levocabastine is a potent, specific and fastacting histamine-Hl-receptor antagonist (1,10,11). In clinical studies using topical administration (eye drops and nasal spray), its efficacy in the treatment of allergic conjunctivitis and allergic rhinitis has been established (2,9).…”
mentioning
confidence: 99%